Taxonomic notes on Exetastes fukuchiyamanus Uchida, 1928 (Hymenoptera, Ichneumonidae, Banchinae), with description of a new species from Japan and China - Watanabe, Kyohei; Sheng, Mao-Ling (Zootaxa, 2018)
Exetastes fukuchiyamanus Uchida, 1928 (Ichneumonidae, Banchinae) is redescribed and its taxonomic status and distribution in Japan and China is reviewed. A new species, E. compressus sp. nov., is described based on specimens collected from China and Japan.